2019
DOI: 10.14814/phy2.14306
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight, but not total, CTRP3 levels are associated with serum triglyceride levels

Abstract: C1q/TNF‐related protein 3 (CTRP3) is a relatively novel adipose tissue‐derived cytokine (adipokine) which has been linked to improved glucose regulation and insulin sensitivity. However, the relationship between circulating CTRP3 levels and diabetes is controversial. CTRP3 can circulate in different oligomeric complexes: trimeric, hexameric, and high molecular weight (HMW) oligomeric complexes. However, the concentration of the different oligomeric complexes in human disease states has not been previously inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our previous work demonstrated that CTRP3 is only found in human circulation as MMW or HMW isoforms [26]; this was also confirmed experimentally in the pediatric study population presented herein (S1 Fig). In addition, Trogen et al [26] found that the differences in the circulating oligomeric forms of CTRP3 had strong correlations with obesity and other metabolic variables, especially circulating triglyceride levels. Therefore, we hypothesized that the MMW and HMW oligometric CTRP3 will be correlated with metabolic variables, specifically circulating serum triglyceride levels.…”
Section: Plos Onesupporting
confidence: 87%
See 4 more Smart Citations
“…Our previous work demonstrated that CTRP3 is only found in human circulation as MMW or HMW isoforms [26]; this was also confirmed experimentally in the pediatric study population presented herein (S1 Fig). In addition, Trogen et al [26] found that the differences in the circulating oligomeric forms of CTRP3 had strong correlations with obesity and other metabolic variables, especially circulating triglyceride levels. Therefore, we hypothesized that the MMW and HMW oligometric CTRP3 will be correlated with metabolic variables, specifically circulating serum triglyceride levels.…”
Section: Plos Onesupporting
confidence: 87%
“…However, it has been speculated that the oligomer conformation of CTRP3 is important for its functional activity [19,22,40,41], and this has been rarely studied. To date only one other study has examined the oligomeric status of CTRP3 with human disease [26]. Trogen et al (2019) determined that all circulating CTRP3 in humans is found as either the MMW or HMW oligomer, with the trimer and monomer of CTRP3 being undetectable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations